Effect of Fermentation Time for Cocoa Beans on the Physicochemical and Organoleptic Characteristics of Dark Chocolate - Putri, Mega Carolina; Maherawati, Maherawati; Hartanti, Lucky (FoodTech: Jurnal Teknologi Pangan, 2025)
Suboptimal cocoa processing is one of the problems in the cocoa industry in West Kalimantan. Cocoa that is processed properly will produce high-value products in the form of dark chocolate. One of the important stages in maintaining the quality of cocoa beans in making dark chocolate is the cocoa bean fermentation process. The purpose of this study was to obtain the fermentation time of cocoa beans that produce dark chocolate with the best physicochemical and organoleptic characteristics. The research design used was a Randomized Block Design (RAK) with one factor, namely the variation of the fermentation time of cocoa beans consisting of 4 treatment levels (without fermentation, 2-day fermentation, 4-day fermentation, and 6-day fermentation). The results showed that the fermentation time of cocoa beans was 6 days, producing cocoa fat of 49.61%, non-fat cocoa solids of 16.22%, total cocoa solids of 65.84%, and a total plate count of 2.4 x 10 ³ colonies/g, and an organoleptic value of aroma of 4.17, an organoleptic value of color of 4.33, an organoleptic value of taste of 4.33 and an overall preference organoleptic value of 4.27.